2019
DOI: 10.1021/acsbiomaterials.9b00678
|View full text |Cite
|
Sign up to set email alerts
|

Guided Regeneration of Rabbit Calvarial Defects Using Silk Fibroin Nanofiber–Poly(glycolic acid) Hybrid Scaffolds

Abstract: Bone tissue engineering aims to regenerate defected bones by combining cells, scaffolds, and growth factors. In general, defected bone tissues are treated with barrier membranes or guiding scaffolds to achieve bone restoration. However, the growth rate of bone tissue is slower than that of adjacent soft tissue. Therefore, we propose patient-customizable guided bone regeneration (GBR) and membrane-guided tissue regeneration (GTR) scaffold hybrid constructs for precise bone tissue restoration without dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Although the aforementioned PGA characteristics make the polymer suitable for high-end applications, such as packaging, electronics, and automobile, so far, it has been mainly used in the biomedical field [ 18 , 19 , 20 ]. The main challenge of the application of PGA is related to its high production cost.…”
Section: Introductionmentioning
confidence: 99%
“…Although the aforementioned PGA characteristics make the polymer suitable for high-end applications, such as packaging, electronics, and automobile, so far, it has been mainly used in the biomedical field [ 18 , 19 , 20 ]. The main challenge of the application of PGA is related to its high production cost.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported the fabrication of silk fibroin (SF) nanofiber membranes and PGA hybrid scaffolds by electrospinning and 3D printing for their use as guided bone tissue regeneration. SF-PGA scaffolds exhibited superior bone volume regeneration compared to scaffolds without nanofiber membranes [88].…”
Section: Poly(glycolic Acid) Pgamentioning
confidence: 96%
“… Scaffolds exhibited co-continuous morphologies with the porosity of ~50 %. Silk fibroin and PGA 121 Bone regeneration  Silk fibroin membranes and PGA based scaffolds prepared by combining electrospinning and hot-melt additive manufacturing.  Within eight weeks, in-vivo rabbit calvarial defect regeneration was achieved.…”
Section: Pga Based Composites In Tissue Engineering and Drug Deliverymentioning
confidence: 99%